Analysis of phenolic compounds in cork from Quercus suber L by HPLC-DAD/ESI-MS - Ana Fernandes (2011)
The aim of the present work was to identify the extractable phenolic compounds present in cork from Quercus suber L The structures of thirty three compounds were tentatively identified by liquid chromatography coupled to electrospray ionisation mass spectrometry (HPLC-DAD/ESI-MS) The majority of those compounds were gallic acid derivatives in the form of either galloyl esters of glucose (gallotannins) combinations of galloyl and hexahydroxydiphenoyl esters of glucose (ellagitannins) dehydrated tergallic-C-glucosides or ellagic acid derivatives Others were found to correspond to low molecular weight phenolic compounds like acids and aldehydes Mongolicain a flavanoellagitannin in which hydrolysable tannin and flavan-3-ol moieties are connected through a carbon-carbon linkage was also detected in cork from Q suber L The results illustrate the rich array of phenolic compounds present in cork